Social, Clinical, and Behavioral Determinants of HIV Infection and HIV Testing among Black Men in Toronto, Ontario: A Classification and Regression Tree Analysis - Djiadeu, Pascal (J Int Assoc Provid AIDS Care, 2020)
Black men bear a disproportionate burden of HIV infection. These HIV inequities are influenced by intersecting social, clinical, and behavioral factors. The purpose of this analysis was to determine the combinations of factors that were most predictive of HIV infection and HIV testing among black men in Toronto. Classification and regression tree analysis was applied to secondary data collected from black men (N = 460) in Toronto, 82% of whom only had sex with women and 18% whom had sex with men at least once. For HIV infection, 10 subgroups were identified and characterized by number of lifetime male partners, age, syphilis history, and perceived stigma. Number of lifetime male partners was the best single predictor of HIV infection. For HIV testing, the analysis identified 8 subgroups characterized by age, condom use, number of sex partners and Chlamydia history. Age (>24 years old) was the best single predictor of HIV testing.